NOVEL CELL WALL DECONSTRUCTION ENZYMES OF THERMOASCUS AURANTIACUS, MYCELIOPHTHORA FERGUSII (CORYNASCUS THERMOPHILUS), AND PSEUDOCERCOSPORELLA HERPOTRICHOIDES, AND USES THEREOF - TSANG, ADRIAN; POWLOWSKI, JUSTIN; BUTLER, GREGORY (2014)
The present invention relates to novel polypeptides and enzymes (e.g., thermostable proteins and enzymes) having activities relating to biomass processing and/or degradation (e.g., cell wall deconstruction), as well as polynucleotides, vectors, cells, compositions and tools relating to same, or functional variants thereof. More particularly, the present invention relates to secreted enzymes that may be isolated from the fungi, Thermoascus aurantiacus strain CBS 181.67, Myceliophthora fergusii (Corynascus thermophilus) strain CBS 405.69, and Pseudocercosporella herpotrichoides strain 494.80. Uses thereof in various industrial processes such as in biofuels, food preparation, animal feed, pulp and paper, textiles, detergents, waste treatment and others are also disclosed. La présente invention concerne de nouveaux polypeptides et de nouvelles enzymes (par exemple des protéines et des enzymes thermostables) ayant des activités associées au traitement et/ou à la dégradation de la biomasse (par exemple la déconstruction de la paroi cellulaire), ainsi que des polynucléotides, des vecteurs, des cellules, des compositions et des outils associés à ceux-ci, ou des variants fonctionnels de ceux-ci. Plus particulièrement, la présente invention concerne des enzymes secrétées qui peuvent être isolées des champignons, de la souche CBS 181.67 de Thermoascus aurantiacus, de la souche CBS 405.69 de Myceliophthora fergusii (Corynascus thermophilus) et de la souche 494.80 de Pseudocercosporella herpotrichoides. L'invention concerne également leurs utilisations dans divers procédés industriels, tels que les biocarburants, la préparation d'aliment, les aliments pour animaux, la pâte et le papier, les textiles, les détergents, le traitement des déchets et d'autres procédés.